Towards Digital TVET: A Comparative Study on Students’ Readiness in The Industry Digital Demands in Indonesia and Malaysia - Kuntadi, Iwa; A, Ana; Rohendi, Dedi; Suryadi, Dedy; Ab Halim, Fazlinda; Ramdani Sari, Ana; Muktiarni; Dwiyanti, Vina (Journal of Technical Education and Training, 2022)
One of the current challenges in the industrial revolution 4.0 is the acceleration of digitalization in vocational education, which is also required to meet various industrial demands, including digital skills. This study aims to measure and analyse the digital skills level possessed by students who have experience in the industry. The study involves two universities, Universitas Pendidikan Indonesia (UPI) and University Tun Hussein Onn Malaysia (UTHM). By using an online questionnaire, 259 students from UPI and UTHM answered 21 questions to measure five digital competence domains as described in the European Digital Competence Framework, which are information, communication, content creation, safety, and problem-solving. Each option on the questions indicates the level of digital competencies measured by scores. The data were analysed using descriptive statistics, such as frequency distribution, mean, standard deviation and independent sample t-test. The result shows that on average, both UPI and UTHM students scored in the intermediate level, with UTHM students scoring slightly higher than UPI students on average. Interestingly, both UPI and UTHM students scored the highest in the information domain and the lowest in problem-solving. It shows that the hypothesis was not accepted as there is a significant difference in the digital skills of the students from both countries. Based on the findings, the result is expected to provide input and improvement in the targeted aspects based on the findings.